Development of novel ssDNA aptamers for detection of receptor-binding domain of SARS-COV-2 - Auti, Amogh; Yadav, Pranay; Bodkhe, Rahul; Bhandari, Yogesh; Varma, Sanjana; Chaudhari, Bhushan; Rahi, Shraddha; Ghormade, Vandana; Vamkudoth, Koteswara Rao (ACS Omega, 2025)
The highly virulent and transmissible SARS-CoV-2 causes COVID-19 and poses a global public health threat. Herein cloned, expressed, and the molecular weight of the receptor-binding domain (RBD) of the SARS-CoV-2 gene encoding protein was confirmed by SDS-PAGE electrophoresis and Western blot analysis. The pivotal aim is to develop single-stranded DNA (ssDNA) aptamers for the rapid detection of SARS-COV-2 infections in humans. In this investigation, a library of nine novel ssDNA aptamers was developed by several rounds of systematic evolution of ligands by an exponential enrichment approach and assessed by an enzyme-linked aptamer assay for binding affinity against RBD antigen (Ag). An in vitro assay resulted in a varied colorimetric signal that depends on the nature of aptamer. Quantitative determination of AptRBD3, AptRBD6, and AptRBD8 aptamers exhibited excellent binding affinity against Ag in the range of 5-10 ng/mL. The putative AptRBD3, AptRBD6, and AptRBD8 aptamers were converted into peptide sequences and docked against RBD, exhibiting good binding energy of -6.8, -6.3, and -7.1 kcal/mol respectively, which were recorded. Furthermore, docking studies of ssDNA aptamers were performed using HDOCK web server to ascertain the binding mechanism and docking score perceived as -389.74, -404.28, and -390.37. Despite this, we engineered a high-affinity AptRBD3.3 aptamer that formed a single and bulged loop, which improved binding affinity, resulted in a docking score of -361.56, and exhibited sensitivity at 4 ng of Ag of SARS-CoV-2. Moreover, computational modeling of AptRBD3.3 revealed an intriguing significant binding affinity with the RBD mutant SARS-CoV-2 S-UK variant (PDB ID: 7EDG) with a docking score of -350.21. In conclusion, the AptRBD3.3 aptamer can be used for the development of lateral flow device and electrochemical sensors for rapid, low-cost, and accurate detection of COVID-19 infection in humans for point of care diagnostics.